Tratamiento de activos intangibles según “Plan BEPS” y su incidencia en la ley del impuesto a la renta peruano - Díaz Ramírez, Alfredo José (2022)
The purpose of this research work was to determine the most appropriate tax treatment of intangible assets according to the Base Erosion Profit Shifting Plan (BEPS Plan) in the Peruvian Income Tax Law, due to the increasing cases of aggressive tax planning. The main objective was to determine whether the Income Tax Law allows a correct treatment of intangible assets. The research was based on a qualitative approach, descriptive in scope, therefore, an analysis of documents was carried out, among them: books, magazines, theses, legal regulations. Consequently, it was concluded that it is necessary to adapt the guidelines in terms of valuation methods, comparability, functional analysis because it influences in a significant way in our Income Tax Law